Mosaic Warfare: from philosophy to model to solutions - Sapaty, P.S (Математичні машини і системи, 2019)
The paper relates to advanced management of large distributed dynamic systems in unpredictable and crisis situations. It briefs the newest DARPA Mosaic Warfare concept oriented on rapidly composable networks of low-cost sensors, multi-domain command and control nodes, and cooperative manned and unmanned systems, with runtime integration of scattered resources which should operate together as one holistic system. It may have the highest value for solving complex national and international defense and security problems for which scattered throughout the world mosaic resources should be quickly integrated to collectively fight disaster and crisis situations, with separate nations unable of doing this individually. The paper shows how distributed mosaic systems can be modeled under the developed Spatial Grasp Technology (SGT) using active distributed knowledge networks, with solving such exemplary problems on them as runtime collection of scattered resources into integral forces operating under unified control, and grouping of certain distributed resources for the surrounding and collective elimination of unwanted phenomena. Стаття присвячена розширеному управлінню великими розподіленими динамічними системами в непередбачуваних і кризових ситуаціях. Викладено новітню концепцію Агентства оборонних проектів (DARPA) Мозаїчні війни, орієнтовану на швидко компоновану мережу сенсорів, багатодоменних вузлів управління, а також спільні пілотовані і безпілотні системи з інтеграцією розкиданих ресурсів, які повинні працювати разом як єдина система. Це може мати особливе значення для вирішення складних національних і міжнародних проблем оборони і безпеки, де розкидані по всьому світу мозаїчні ресурси повинні швидко об’єднуватися для колективної боротьби з лихами і кризами, оскільки окремі країни не в змозі здійснювати це самостійно. Показано, як розподілені мозаїчні системи можна моделювати за допомогою розробленої Технології просторового захоплення (ТПЗ), яка використовує активні розподілені мережі знань, вирішуючи такі проблеми, як збір і інтеграція в реальному часі поширених ресурсів під єдиним управлінням і групування таких ресурсів для колективної ліквідації небажаних явищ. Статья посвящена расширенному управлению большими распределенными динамическими системами в непредсказуемых и кризисных ситуациях. Изложена новейшая концепция Агентства оборонных проектов (DARPA) Мозаичные войны, ориентированная на быстро компонуемые сети сенсоров, многодоменных узлов управления, а также совместные пилотируемые и беспилотные системы с интеграцией разбросанных ресурсов, которые должны работать вместе как единая система. Это может иметь особое значение для решения сложных национальных и международных проблем обороны и безопасности, где разбросанные по всему миру мозаичные ресурсы должны быстро объединяться для коллективной борьбы с бедствиями и кризисами, поскольку отдельные страны не в состоянии осуществлять это самостоятельно. Показано, как распределенные мозаичные системы можно моделировать с помощью разработанной Технологии пространственного захвата (ТПЗ), использующей активные распределенные сети знаний, решая такие проблемы, как сбор и интеграция в реальном времени распространенных ресурсов под единым управлением и группирование таких ресурсов для коллективной ликвидации нежелательных явлений.